Probability and statistics a didactic introduction - Barragués, José I.; Morais, Adolfo; Guisasola Aranzabal, Jenaro (CRC Press/Taylor & Francis Group, 2014)
Probability and Statistics concepts are constructed as they are needed for the solving of new problems. - Self-assessment activities have been proposed throughout the chapter, not just at the end. The aim of these activities is to involve the reader in actively participating in the construction of the theoretical framework, so that the reader reflects on the meanings that are being constructed, their utility and their practical applications. - Examples of applications, solved problems and additional problems for readers have been provided. - Paying attention to potential students' learning difficulties. Some of these have been widely studied by the research community in the field of Mathematics Education. - Including activities that use the computer to explore the meaning of the concepts in greater depth, to experiment or to investigate problems. We would like to thank the authors for the interest and care that they have shown in completing their work. They have brought not only their knowledge of the discipline, but also valuable experience in university teaching and current practical applications of Probability and Statistics. José Barragués, Adolfo Morais Jenaro Guisasola"